Investigation of a root zone heating system for greenhouse seedling and its effects on micro-environment - He, Fen; Hou, Yong; Li, Kai; Wei, Xiaoming; Liu, Yaqing (International Journal of Agricultural and Biological Engineering, 2020)
Under the extremely cold climatic condition, crops have to survive severe heat stress conditions, even if they are being kept in greenhouses. In the winter and spring of North China, the air and soil temperature is low inside the greenhouse, and when using a traditional heating system, the energy consumption is high. This paper reports on a study of different design solutions for a root zone heating system based on a kind of low temperature radiation material. Root zone heating systems offer increasing crop quality and productivity. A novel type of heat preservation and root zone heating system was applied in greenhouse seedling. And through multiple experiments, the effect of the root zone heating system on the ambient environment and seedbed surface was studied, and the heat preservation effect and heating uniformity were discussed. Results show that single-layer film covering on the root zone heating system can make the average temperature at night increase 1°C. And the average seedbed surface and substrate temperature can increase 11.3°C and 5.2°C, respectively. In conclusion, the root zone heating system can effectively improve the environmental temperature of seedling and the uniformity of heating is high, which provides a strong guarantee for high-quality seedling cultivation. Keywords: greenhouse, root zone heating system, micro-environment, seedling, substrate temperature, air temperature DOI: 10.25165/j.ijabe.20201306.5905 Citation: He F, Hou Y, Li K, Wei X M, Liu Y Q. Investigation of a root zone heating system for greenhouse seedling and its effects on the micro-environment. Int J Agric & Biol Eng, 2020; 13(6): 47–52.